2019
DOI: 10.1159/000502652
|View full text |Cite
|
Sign up to set email alerts
|

International Society for Nutritional Psychiatry Research Practice Guidelines for Omega-3 Fatty Acids in the Treatment of Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a complex mental illness with unmet therapeutic needs. The antidepressant effects of ω–3 polyunsaturated fatty acids (n–3 PUFAs) have been widely reported. The subcommittee of the International Society for Nutritional Psychiatry Research organized an expert panel and conducted a literature review and a Delphi process to develop a consensus-based practice guideline for clinical use of n–3 PUFAs in MDD. The guideline focuses on 5 thematic areas: general concepts, acute treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 82 publications
2
113
0
Order By: Relevance
“…It was mentioned that this index plays a pathophysiologic role in depressive symptoms [ 45 , 49 , 50 ]. The International Society for Nutritional Psychiatry Research Practice Guidelines for ω-3 fatty acids has recently recommended therapeutic dosages of pure EPA or a combination of EPA and DHA (with net EPA starting from at least 1 up to 2 g/day) for at least eight weeks as a potential treatment for major depressive disorders [ 51 ]. We have previously shown that low omega-3 index in pregnancy is a possible risk factor for postpartum depression [ 52 ], with a cut-off at 4%.…”
Section: Discussionmentioning
confidence: 99%
“…It was mentioned that this index plays a pathophysiologic role in depressive symptoms [ 45 , 49 , 50 ]. The International Society for Nutritional Psychiatry Research Practice Guidelines for ω-3 fatty acids has recently recommended therapeutic dosages of pure EPA or a combination of EPA and DHA (with net EPA starting from at least 1 up to 2 g/day) for at least eight weeks as a potential treatment for major depressive disorders [ 51 ]. We have previously shown that low omega-3 index in pregnancy is a possible risk factor for postpartum depression [ 52 ], with a cut-off at 4%.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that n‐3 PUFA supplements may be less effective in individuals at risk for depression than in currently depressed patients. Recently, the International Society for Nutritional Psychiatry Research Practice has formulated guidelines for the use of n‐3 PUFA supplementation in the treatment and prevention of MDD (Guu et al, 2019). In response, we argued that there is indeed some evidence from RCTs for the usefulness of n‐3 PUFA supplementation in the treatment of clinically depressed cases, but there is not enough evidence from RCTs on the usefulness of n‐3 PUFA supplementation in the prevention of depression in at‐risk individuals (Thesing, Lamers, Bot, Penninx, & Milaneschi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Su et al revealed that a high dose of n-3 PUFAs (4400 mg EPA + 2200 mg DHA per day) had a significantly decreased score on the 21-item Hamilton Depression Rating Scale (HDRS) [7]. However, the effects of a high dose of DHA on depression are still unclear [8][9][10], because most of the evidence supports the theory of EPA superiority [11,12]. Before effective doses of n-3 PUFA were recommended based on the results of head-to-head trials for MDD patients, comparative effectiveness research is necessary to identify the efficacy of different doses of n-3 PUFA supplementation.…”
Section: Introductionmentioning
confidence: 99%